2019
DOI: 10.1186/s12889-019-7534-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B vaccination coverage across India: exploring the spatial heterogeneity and contextual determinants

Abstract: Background Although hepatitis B vaccinations have been integrated in the Universal Immunization Program (UIP) in India over a decade, only half of the children are immunized against hepatitis B. The national average in hepatitis B vaccination conceals large variations across states, districts and socio-economic groups. In this context, the aim of this paper is to examine the spatial heterogeneity and contextual determinants of hepatitis B vaccination across the districts of India. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 25 publications
4
40
0
Order By: Relevance
“…This suggests that more male patients are on hemodialysis and CKD is also more common CKD patients and education in a study conducted by Amjad et al 14 , which differs from our results. Studies from the general population and healthcare workers showed that education was significantly associated with vaccination status against HBV, comparable to our results [24][25][26] . Individuals who have more education may be better aware of the preventive role of vaccination, which may be the cause of better vaccination status in higher educated people.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that more male patients are on hemodialysis and CKD is also more common CKD patients and education in a study conducted by Amjad et al 14 , which differs from our results. Studies from the general population and healthcare workers showed that education was significantly associated with vaccination status against HBV, comparable to our results [24][25][26] . Individuals who have more education may be better aware of the preventive role of vaccination, which may be the cause of better vaccination status in higher educated people.…”
Section: Discussionsupporting
confidence: 91%
“…This is the same as the United States Renal Data System 2011 Annual Data Report that showed that the initiation of dialysis was much higher in males as compared to females 18 . However, a meta-analysis reported that in some studies CKD was more common in females, while in other was significantly associated with vaccination status against HBV, comparable to our results [24][25][26] . Individuals who have more education may be better aware of the preventive role of vaccination, which may be the cause of better vaccination status in higher educated people.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, checking the pattern of missing we found that the missing pattern is not random (MAR) and thus we could not impute. Though we followed the DHS guidelines, another limitation of vaccination data from National family Health Survey is that it is based upon mother's recall when vaccination card not found at the time survey, which introduces a non-sampling bias in the estimation process 50,51 . Additionally, the dataset lacks the information on cause specific mortality and in a country like India, diarrhoeal infection, acute respiratory infection and low utilization of post natal care largely contributes to child mortality 37,52,53 with state and regional variation to which we could not adjust while compiling the infant and child mortality rates to execute the district level meso scale analysis.…”
Section: Discussionmentioning
confidence: 99%